PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN LONG TERM DEBT TO ASSET RATIO TERHADAP PAJAK PENGHASILAN BADAN TERUTANG (Studi Empiris Pada Perusahaan yang Terdaftar di BEI Tahun 2015-2019) - Kumba Digdowiseiso; Bambang Subiyanto; Kennedy Irnandi (Jurnal Akuntansi dan Pajak, 2022)
This study aims to investigate the effects of Current Ratio (CR), Debt to Equity Ratio (DER), and Long term Debt to Asset Ratio (LDAR) on Corporate Income Tax Payable in companies listed on the Indonesia Stock Exchange LQ45. We use a quantitative method by utilizing a multiple linear regression to analyze the nexus between independent variable and dependent variable. Based on the predetermined criteria set in the purposive sampling technique, 10 companies were selected from the LQ45 index on the Indonesia Stock Exchange (IDX) over the period 2015-2019. Our findings indicate that both Current Ratio (CR) and Debt to Equity Ratio (DER) have a positive and significant effect on Corporate Income Tax Payable. Meanwhile, Long-Term Debt to Asset Ratio (LDAR) has no significant effect on Corporate Income Tax Payable.